ANALISIS YURIDIS TERHADAP KOMPETENSI PENGADILAN HUBUNGAN INDUSTRIAL DALAM MEMERIKSA SENGKETA PERJANJIAN KEMITRAAN - Cherya Metriska; Yogo Pamungkas (Fakultas Hukum Universitas Trisakti, 2021)
The definition of absolute competence is regarding to power between judicial bodies, seen from the type of court, and regarding the granting of power to adjudicate. The research’s main problems are whether the Central Jakarta Industrial Relations Court has the authority to examine and decide disputes between Wandi Irawan, et al., Against PT Tubagus Jaya Mandiri and whether the decision of Industrial Relations Court in the dispute between Wandi Irawan, et al and PT Tubagus Jaya Mandiri complies with Law Number 2 of 2004? This research is a normative and descriptive analytical legal research by using secondary data and the conclusions are drawn by using deductive logic methods. The conclusions are that the Industrial Relations Court at the District Court in the first degree had been decided with a N.O Decision or an unacceptable decision, because it is clear that when it comes to a claim containing or violating absolute competence, the claim is said to be unacceptable, not rejected decison so that the plaintiff should have re-submitted the lawsuit to District Court in the legal area where the defendant lives, not to Industrial Relations Court because it is not an institution that has the authority to adjudicate.